Section in the openings of Sur (The star, the pen, and the Morning Hours) Objective study - Hasan, Salam Abbood (International Journal of Psychosocial Rehabilitation, 2020)
Praise be to God, and may blessings and peace be upon the Messenger of God and his good and pure family and righteous companions, and on those who followed their path until the Day of Judgment, and after... For in the Holy Qur’an there are huge treasures of references, sins, revelations, meanings, facts and connotations, as scholars accept the Holy Qur’an, and they enjoy what God opens to them from these sects, meanings and facts, and the Commander of the Faithful Ali bin Abi Al-Alb (peace be upon him) was authenticated in his description of the Qur’an, He says: ((There is a report about what came before you, and what is after you, and the judgment of what is between you ... It is the strong rope of God, which is the wise remembrance, and it is the straight path, and it is the passions that do not pass through the passions or the confusion of the tongues, and the scholars are not satisfied with it nor created by many the response and its wonders do not expire, whoever says he is truthful, whoever works for it is rewarded, whoever rules it is just, and who is called To him was guided to a straight path)).